2010
DOI: 10.1016/j.tetlet.2009.12.141
|View full text |Cite
|
Sign up to set email alerts
|

Proline-like β-turn mimics accessed via Ugi reaction involving monoprotected hydrazines

Abstract: A four-center, three-component Ugi-type reaction of a variety of keto acids, Boc-or Cbz-protected hydrazine, and isocyanides offers a simple and high-yielding access to cyclic products containing an N-aminolactam unit. The latter are shown to form consistently an intramolecular hydrogen bond leading to a -turn-like secondary structure. The possibility of integrating such N-aminolactam units (without disruption of the folded structure) into pseudotripeptide fragments is demonstrated.The successful use of keto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…27,28 In particular, we have evaluated the Ugi organic transformation, 33,34 which involves the condensation among four substrates, in this case a carbonylderivate, an amine, a carboxylic acid, and an isocyanide to form α-aminoacyl amide derivatives, which are important in the pharmaceutical industry and fine chemistry to develop organic drug-like molecule libraries. [35][36][37] Out of the evaluated MOFs we found that those with a suitable ratio of acid and basic sites in their structure displayed the best catalytic performance. 27 Both, InPF-50, and -51, are formed by SBUs composed of only one metal cation, with accessible acid sites.…”
Section: Catalytic Resultsmentioning
confidence: 95%
“…27,28 In particular, we have evaluated the Ugi organic transformation, 33,34 which involves the condensation among four substrates, in this case a carbonylderivate, an amine, a carboxylic acid, and an isocyanide to form α-aminoacyl amide derivatives, which are important in the pharmaceutical industry and fine chemistry to develop organic drug-like molecule libraries. [35][36][37] Out of the evaluated MOFs we found that those with a suitable ratio of acid and basic sites in their structure displayed the best catalytic performance. 27 Both, InPF-50, and -51, are formed by SBUs composed of only one metal cation, with accessible acid sites.…”
Section: Catalytic Resultsmentioning
confidence: 95%
“…[19] The Ugi four-component reaction( U-4CR) is perhaps oneo f the most important isocyanide-based MCRs. [19][20] It is avaluable methodf or generating a-aminoacyl amide derivatives in av ery straightforward manner by the condensation of an aldehyde, amine, carboxylic acid, and isocyanide in ao ne-pot reaction. [18] Lewis acids are not alwaysr equired for many of the reported isocyanide-based MCRs;h owever,t oo btain good yields and selectivity in the U-4CR,L ewis acid catalysts do have to be used.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports on the use of hydrazones in Ugi reactions [1423], however, to the best of our knowledge, there is no report involving α-hydrazonocarboxylic acids.…”
Section: Resultsmentioning
confidence: 99%